Study Camp Based Computational Thinking Assistance to Improve Mathematical Literacy at Madrasah Tsanawiyah, Padang City - Lilis Harianti Hasibuan; Darvi Mailisa Putri; Ida Royani; Lisa Susanti; Latifatul Qalbi (Bakti Cendana, 2026)
Literacy is an essential competency in responding to rapid technological advancements. Mathematical literacy enables students to understand, analyze, and apply mathematical concepts in various real-life contexts. This community service program aimed to strengthen students’ mathematical literacy through computational thinking assistance implemented in a study camp format. The activity adopted a Community-Based Research (CBR) model consisting of four stages: laying the foundation, planning, information gathering and analysis, and acting on findings. The study camp was conducted in a laboratory setting, beginning with the introduction of basic programming concepts and continuing with computational thinking exercises integrated into mathematical literacy problems. This approach is expected to foster students’ critical thinking skills and enhance their mathematical competencies through interactive and technology-based learning experiences.